Online Learning Through The RADEC Model to Increase HOTS of Elementary School Students in The Time of The Covid-19 Pandemic - Pratama, Yoga Adi; Dewi, Laksmi (PrimaryEdu : Journal of Primary Education, 2022)
During the Covid-19 pandemic, thinking skills-oriented learning has not been implemented properly, the impact of student HOTS is getting lower. The purpose of this study is to increase the HOTS of elementary school students during the Covid-19 pandemic through the RADEC learning model. The research was conducted at SDN Harapan 1 Cimahi City. The research methodology uses classroom action research. Data collection techniques used are tests and observations. Data analysis used comparative analysis techniques and qualitative analysis. The results showed that there were only 2 students in the pre-cycle data that obtained the "good" criteria, in the first cycle it increased significantly to 15 students, and in the second cycle it increased again to 20 students. Furthermore, in the pre-cycle students who completed it reached 13 students (37.1%), in the first cycle increased to 28 students (80%), and the second cycle by 33 students (94.2%) who completed. This significant increase is because the entire syntax of the HOTS-oriented RADEC learning model can be easily implemented during the Covid-19 pandemic because the syntax is flexible, adaptive, and in accordance with the characteristics of Indonesian students. The conclusion of this study is that the RADEC learning model can increase the HOTS of grade IV students at SDN Harapan 1 for the 2020/2021 academic year during the Covid-19 pandemic.